Indoor radon concentration measurements in workplaces and their impact on health risk assessment. Issue 4 (April 2023) - Loffredo, Filomena; Quarto, Maria
Radon is the main source of exposure to ionizing radiation for the general population. In Italy, very little has been investigated to determine occupational radon exposure in workers. In this study, radon concentrations of various workplaces type were measured for 1 year using SSNTD CR-39. Q–Q plot and Shapiro–Wilks statistical test showed that radon concentrations are not log-normally distributed. The geometric mean of radon concentration was found to be 97 Bq/m 3 with a geometric standard deviation of 3. The mean effective dose to workers has been calculated and found to be 1.4 mSv/y. Finally, for estimation of cancer risks, the lifetime risk and lung cancer cases per year per million have been calculated.